Kajian Pengaruh Geometri Jalan Terhadap Konsumsi Bahan Bakar Alat Angkut pada Jalan Tambang Quarry Batu Andesit di PT Silva Andia Utama Desa Giri Asih, Kecamatan Batujajar, Kabupaten Bandung Barat, Provinsi Jawa Barat - Taufiq Maulana Akbar; Iswandaru; Noor Fauzi Isniarno (Bandung Conference Series: Mining Engineering, 2023)
Abstract. PT Silva Andia Utama is a company engaged in the andesite mining industry, using the Quarry mining method. PT Silva Andia Utama has set a production target of 637.2 BCM/day or 95.18 BCM/hour. However, the production target was not achieved due to several factors, one of which is the road geometry factor in the field including road width, road slope, cross slope, superelevation, and bend radius. this also affects the use of fuel in dump truck engines so there may be a potential for swelling in operational costs, especially in terms of fuel costs. Therefore, it is necessary to study the geometry of the mining road so that production targets are achieved and maximize fuel use and minimize operational costs, especially fuel costs. This research was conducted by observing the hauling process from the loading point to the dumping point with a distance of 0.60 km and divided into 23 road segments. The actual data taken includes road width, road slope, cross slope, superelevation, corner radius, cycle time, productive time, fill factor, swell factor, and fuel consumption of mechanical devices. Then calculations for the production of loading and transportation equipment, fuel consumption, fuel ratio, and fuel costs are carried out so that the actual calculation results are compared with the calculations after repairs following Ministerial Decree 1827 K/30/Mem/2018 and the American Association of State Highway and Transportation Officials (AASHTO). Based on the calculations, the average production of the means of transportation is 86.76 BCM/hour with fuel consumption of 5.62 liters/hour for the means of transportation. The actual average fuel ratio of the means of transportation of 0.26 liters/BCM and the actual fuel consumption per trip of the means of transportation is 1.06 liters/rite. The actual fuel cost of the conveyance is Rp. 16,113,000. After re-evaluating the road geometry following the Ministerial Decree 1827 K/30/MEM/2018 standard by changing the slope from 13.42% - 21.22% to a maximum of 12% so that the travel time for transportation equipment becomes faster. For the production of transportation equipment after the repair of 108.54 BCM/hour, there was an increase of 26.25%, the fuel consumption of the transportation equipment after the repair was 4.45 liters/hour there was a decrease of 20.82%, and the fuel consumption per iteration after the repair was 0. 66 liter/rite decreased 37.73%. The fuel ratio after repairs for transportation equipment is 0.16 liters/BCM and for transportation equipment fuel costs after repairs are Rp. 10,136,622 decreased by 37.09%. Abstrak. PT Silva Andia Utama merupakan salah satu perusahaan yang bergerak dalam industri pertambangan bahan galian batu andesit dengan menggunakan metode penambangan Quarry. PT Silva Andia Utama menetapkan target produksi sebesar 637,2 BCM/hari atau 95,18 BCM/jam. Akan tetapi, target produksi tersebut tidak tercapai dikarenakan beberapa faktor salah satunya yaitu faktor geometri jalan yang ada di lapangan meliputi lebar jalan, kemiringan jalan, cross slope, super elevasi dan jari-jari tikungan. hal ini juga mempengaruhi penggunaan bahan bakar pada mesin dumptruck sehingga sangat mungkin memiliki potensi terjadi pembengkakan pada biaya operasional khususnya bagian biaya bahan bakar. Oleh karena itu, diperlukan kajian mengenai geometri jalan tambang agar target produksi tercapai dan memaksimalkan penggunaan bahan bakar serta dapat meminimalisir pengeluaran biaya oprasional khususnya pada biaya bahan bakar. Penelitian ini dilakukan dengan mengamati proses hauling dari loading point menuju dumping point dengan jarak 0,60 km dan terbagi menjadi 23 segmen jalan. Data yang diambil secara aktual meliputi lebar jalan, kemiringan jalan, cross slope, superelevasi, jari-jari tikungan, cycle time, waktu produktif, fill factor, swell factor, dan konsumsi bahan bakar alat mekanis. Kemudian dilakukan perhitungan produksi alat muat dan alat angkut, konsumsi bahan bakar, fuel ratio dan fuel cost sehingga hasil perhitungan aktual dibandingkan dengan perhitungan setelah perbaikan sesuai dengan standar Kepmen 1827 K/30/Mem/2018 dan American Association of State Highway and Transportation Officials (AASHTO). Berdasarkan perhitungan, diperoleh rata-rata produksi alat angkut sebesar 86,76 BCM/jam dengan konsumsi bahan bakar untuk alat angkut sebesar 5,62 liter/jam. Untuk rata-rata fuel ratio aktual alat angkut sebesar 0,26 liter/BCM dan konsumsi bahan bakar per ritase aktual alat angkut 1,06 liter/ritase. Fuel cost aktual alat angkut sebesar Rp. 16.113.000. Setelah dilakukan evaluasi kembali terkait dengan geometri jalan sesuai dengan standar Kepmen 1827 K/30/Mem/2018 dengan mengubah kemiringan dari 13,42% - 21,22% menjadi maksimal 12% sehingga waktu tempuh alat angkut menjadi lebih cepat. Untuk produksi alat angkut setelah perbaikan sebesar 108,54 BCM/jam terjadi kenaikan 26,25%, konsumsi bahan bakar alat angkut setelah perbaikan adalah 4,45 liter/jam terjadi penurunan 20,82% dan konsumsi bahan bakar per ritase setelah perbaikan 0,66 liter/ritase terjadi penurunan 37,73%. Fuel ratio setelah perbaikan untuk alat angkut sebesar 0,16 liter/BCM dan untuk fuel cost alat angkut setelah perbaikan sebesar Rp. 10.136.622 terjadi penurunan 37,09%.